Advantages Of Temporary Waqf In Combating Covid-19 Pandemic In Malaysia - Muhammad Ainul Hakim Muhammad Khalil; Azman Ab. Rahman; Muhamad Firdaus Ab Rahman; Hussein 'Azeemi Abdullah Thaidi (Faculty of Syariah and Law, Universiti Sains Islam Malaysia, 2024)
International Seminar on Syariah and Law (INSLA 2020) E-Proceedings “Hala Tuju Syariah Dan Undang - Undang Mendepani Pandemik Covid - 19” Organized by : Faculty of Syariah and Law, Universiti Sains Islam Malaysia 27-28 October 2020